Tuer à la guerre chez Xénophon : normalité, joie et indignation relative - Lennart Gilhaus (Kentron, 2023)
In war, people kill. Killing in war is constantly present in ancient historiography, but rarely explicitly addressed. Nevertheless, a closer look reveals quite different and contradictory attitudes towards the act of killing in war. This article will attempt to work out, on the basis of Xenophon’s writings, under which circumstances killing in war is presented as a normal act, hailed as a cause for joy or criticised as shameful. Xenophon seems to have been very flexible in his assessments: for him, the end often justified the means. At the same time, he always demanded to pay attention to the consequences of the use of violence.